2011
DOI: 10.1038/aps.2011.86
|View full text |Cite
|
Sign up to set email alerts
|

Proteome reference map and regulation network of neonatal rat cardiomyocyte

Abstract: Aim: To study and establish a proteome reference map and regulation network of neonatal rat cardiomyocyte. Methods: Cultured cardiomyocytes of neonatal rats were used. All proteins expressed in the cardiomyocytes were separated and identified by two-dimensional polyacrylamide gel electrophoresis (2-DE) and matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS). Biological networks and pathways of the neonatal rat cardiomyocytes were analyzed using the Ingenuity Pathway Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Thus the IPA was a very important tool for filtering our results and identifying possible links for biological systems, thus providing a better understanding of protein interactions between NS4B and cellular proteins such as CypA. IPA can identify both relevant cellular pathways and mechanisms through which proteins are involved, thus enabling attests for hypotheses and validation experiments for complex data. …”
Section: Results and Discussionmentioning
confidence: 99%
“…Thus the IPA was a very important tool for filtering our results and identifying possible links for biological systems, thus providing a better understanding of protein interactions between NS4B and cellular proteins such as CypA. IPA can identify both relevant cellular pathways and mechanisms through which proteins are involved, thus enabling attests for hypotheses and validation experiments for complex data. …”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, induction of myocardial CTGF mRNA and protein in pigs with heart failure was not a decisive effector in fibrosis 19 . CTGF is a growth factor and has 4 modules, each of which interacts with different proteins and regulates many physiological processes 4 . Therefore, CTGF may also have an unknown function for maintaining cardiac physiological actions other than enhancement of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis (IPA) software to predict cardiac functions by using two-dimensional electrophoresis data of protein extracts from cultured neonatal rat cardiomyocytes 4 and to identify target mRNAs involved in mouse cardiac hypertrophy 5 . IPA uses a database of the scientific literature to predict pathways, upstream regulators, and biological functions relevant to the uploaded data set and to provide biological interpretations and their statistical probabilities.…”
Section: Several Studies Have Utilized Ingenuity Pathwaymentioning
confidence: 99%
“…Large-scale protein-protein interaction maps provide new insights into protein functions, pathways, molecular machines and functional protein modules. 17 Moreover, studies have indicated that protein-protein interaction networks are vital to understanding disease specificity. 18 Recent advances in highthroughput methods for taking global measurements of protein levels from biological samples have driven the field of systems biology.…”
Section: Discussionmentioning
confidence: 99%
“…24 Recent studies have also shown that house-keeping proteins and tissue-specific proteins have different topological properties in the human protein-protein interaction network. [25][26][27][28] Several studies of protein interaction networks have focused on detecting highly connected protein modules which generally correspond to meaningful biological units such as protein complexes and functional modules. 29 However, biological networks including protein-protein interaction networks are generally very sparse.…”
Section: Discussionmentioning
confidence: 99%